PHYSICAL QUALITY OF ELEPHANT GRASS (Pennisetum purpureum) SILAGE ON DIFFERENT LEVELS OF Indigofera zollingeriana LEAF MEAL ADDITION - R., Nurcahyati; Cakra, I G. L. O.; Trisnadewi, A. A. A. S. (Jurnal Peternakan Tropika; Vol 12 No 1 (2024): Vol. 12 No. 1 Tahun 2024; January - February, 2024)
This study aimed to determine the effect of the addition of Indigofera leaf meal on the physical quality of elephant grass ( Penisetum purpureum ) silage. This research was conducted at the Sesetan Research Station and Animal Feed Laboratory, Faculty of Animal Husbandry, Udayana University. This study conducted for one month, using a completely randomized design consisted of four treatments and five replications. The treatments consisted of R1 (95% elephant grass + 5% molases + 0% Indigofera leaf meal), R2 (85% elephant grass + 5% molases + 10% Indigofera leaf meal) R3 (75% elephant grass + 5% molases + 20% Indigofera leaf meal), and R4 (65% elephant grass + 5% molases + 30% Indigofera leaf meal). The variabel observed were: color, smell, texture, the presence of mold and silage pH. pH value data was analyzed with analysis of variance and physical quality data were analyzed using a frequency distribution. The results showed that the addition of Indigofera leaf meal to elephant grass silage ( Pennisetum purpureum ) up to a dose of 30% showed no difference in the physical quality of elephant grass silage. The conclusion of this study is the addition of Indigofera meal to elephant grass silage has no effect on the physical quality of the silage.